ANALISIS PEREKONOMIAN DAERAH DAN PENDAPATAN ASLI DAERAH KABUPATEN/KOTA DI PROVINSI SUMATERA BARAT (JURNAL ECONOMICA : Research of Economic And Economic Education, 2012)
This study aims to identify and analyze: 1) the effect of household consumption, private investment, and development spending revenue to the regional economy, 2) the effect of private investment, construction spending, employment and regional economy on local income. This study is an exploration studies conducted throughout the Kabupaten/Kota is as much as 19 districts / cities in West Sumatra province. Years of the study period was 2005 to 2009 (5 years).The study found that: 1) household consumption, private investment, and development spending revenue simultaneously or partially significant effect on the regional economy regencies / cities in West Sumatra province. The higher the level of household consumption of a region, the allocation of development spending is high, the amount of private investment that invested in the area and the higher revenues will be able to improve the condition of the local economy. 2) Private investment, construction spending, employment and regional economy simultaneously and partially significant effect on revenue Kabupaten/Kota in West Sumatra province. A growing number of private parties to invest in the area, the size of the allocation of development funds for various public sector facilities, the more labor is absorbed by the sector of the economy will be able to increase local income. Penelitian ini bertujuan untuk mengetahui dan menganalisis: 1) Pengaruh konsumsi rumah tangga, investasi swasta, belanja pembangunan dan pendapatan asli daerah terhadap perekonomian daerah, 2) Pengaruh investasi swasta, belanja pembangunan, tenaga kerja dan perekonomian daerah terhadap pendapatan asli daerah.